(untitled) - Hipsher, Scott A. (London, 2010)
This is an international business study of Theravada Buddhist Southeast Asia. Using a cross-disciplinary approach, the book examines business practices within a political, cultural, economic and religious context. It highlights those cultural and historical ties of the region which are shared because of a common religion. In analysing business environments, economics and government practices across the region, the book provides a deeper understanding of the influence of cultural values on work practices in Southeast Asia. The author first offers an overview of the history of the region and the nature and guiding principles of Theravada Buddhism. The next sections of the book present the history and the business and economic environment of the four countries in Southeast Asia, along with some relevant case studies of Cambodia, Laos, Myanmar/Burma and Thailand. The book analyses business strategies and practices, management and marketing issues as well as the characteristics of companies. The last part considers the political environment of the four countries and hints at future trends and developments. The book offers a framework for working in the region, and provides valuable insights into this unique business environment, which is significantly different from the Western context. Filling a gap in existing literature, this book provides an accessible study of actual business practices in Southeast Asia.
Keywords: Business etiquette,Hình thức kinh doanh; Đông Nam Á; Southeast Asia